Gómez-Pellón, Eloy (ed.) (2018). Rural worlds, social sustainability and local landscapes in the globalisation era. Case studies in Southern Europe - Díaz Soria, Inmaculada (Documents d’Anàlisi Geogràfica, 2020)
Gómez-Pellón, Eloy (ed.) (2018) Rural worlds, social sustainability and local landscapes in the globalisation era. Case studies in Southern Europe Cizur Menor: Editorial Aranzadi, 315 p. ISBN 978-84-9177-067-1